(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article represents a short organization and technological analysis of finalizing the construction, using both conventional work materials and modern lightweight structures of fast assembling. The studies are done on the basis of «L» teaching block, which is in Poltava National Technical Yuri Kondratyuk University. Results of the study showed that it needs reconstruction. All-inclusive organization and technological and economical comparison of these two variants of the buildup proved that it is more advanced to carry out building works using modern technologies, even though they need more manpower effort and are more expensive. Nowadays we can observe a tendency to widely use fast mounting structures and it will only become more wide-spread in the future, which will inevitably result in both technologies and engineer construction equipment cheapening. Keywords: reconstruction, erecting, conventional work materials, light gauge steel framing, thermal modernization.